THE ROLE OF VEGFA GENE POLYMORPHISM IN DIABETIC FOOT SYNDROME DEVELOPMENT - A. V. Rusanov; Ya. D. Chumachenko (Східноукраїнський медичний журнал, 2019)
Introduction. The dysfunction of vascular endothelial growth factor A (VEGFA) is one of the leading factor of macro- and microangiopathy development in diabetic foot syndrome (DFS) patients. Recently, a number of experimental studies in various populations have been carried out to test the association between VEGFA gene polymorphisms and development of chronic hyperglycemia vascular complications. At the same time, there are no such studies in Ukrainian population.